A method for two-step joining of alumina ceramics based on the principle of alumina powder solder sintering and glass infiltration

CN118754698BActive Publication Date: 2026-10-23CHANGCHUN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411015868.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-26
Publication Date
2026-10-23
Estimated Expiration
2044-07-26

AI Technical Summary

Technical Problem

然而,在焊料中引入高熔点相将不可避免地导致焊料流动性的降低,从而导致孔隙缺陷的形成,限制了这一方法的应用

Benefits of technology

[0021] 1. The method of this invention first uses the sintering principle to connect alumina ceramics with alumina powder. Then, utilizing the principle of liquid glass penetrating into the intergranular space of dense ceramics, glass solder is used to penetrate and fill the alumina/porous Al2O3/alumina joint to eliminate weld defects, reduce thermal expansion differences, and improve the high-temperature resistance and thermal shock resistance of the joint, ultimately obtaining a joint with high strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118754698B_ABST
    Figure CN118754698B_ABST
Patent Text Reader

Abstract

The application discloses a two-step connecting method of alumina ceramic based on the sintering of alumina powder solder and the glass infiltration principle, and belongs to the technical field of welding. The method is characterized in that: firstly, alumina powder is used to connect alumina ceramic; and then, glass solder is used to fill the holes (including open holes and closed holes) in the welding seam, so that a dense welding seam layer is obtained. The Al2O3 phase content in the alumina / alumina joint welding seam obtained by the method is higher than 50%, and the difference between the thermal expansion coefficients of the welding seam and the base material is less than 2%. The joint has excellent mechanical properties, high-temperature resistance and thermal shock resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of welding technology, and specifically to a two-step method for joining alumina ceramics based on the principles of alumina powder solder sintering and glass infiltration. Background Technology

[0002] Alumina ceramics possess numerous advantages, including high hardness, high strength, high toughness, and excellent corrosion resistance, making them widely used in machinery, chemical, and aerospace industries. However, due to the inherent brittleness and difficulty in machining of ceramic materials, joining techniques are often required to construct complex shapes and large-sized ceramic components.

[0003] Among various methods for joining ceramic materials, glass solder is more suitable for joining ceramics due to the good chemical compatibility between glass and ceramics. However, the principle of traditional glass joining methods is similar to brazing, and the microstructure and physicochemical properties of the weld are significantly different from those of the base material. For example, the coefficient of thermal expansion, elastic modulus, and softening temperature of the weld are all significantly different from those of the ceramic base material, resulting in insufficient thermal shock resistance and high-temperature resistance of the joint. Adding a high-melting-point second phase to the glass solder is an effective method to improve the high-temperature resistance of the joint. In particular, adding a powder with the same chemical composition as the base material as a second phase to the solder can not only improve the high-temperature resistance of the joint but also reduce the difference in the coefficient of thermal expansion between the base material and the weld. However, introducing a high-melting-point phase into the solder will inevitably lead to a reduction in solder fluidity, resulting in the formation of porosity defects, which limits the application of this method. Summary of the Invention

[0004] The purpose of this invention is to provide a two-step method for joining alumina ceramics based on the principles of alumina powder solder sintering and glass infiltration, to obtain welds with high Al2O3 content, eliminate weld porosity defects, and thereby improve joint strength, thermal shock resistance and high temperature resistance.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0006] A two-step method for joining alumina ceramics based on the principles of alumina powder solder sintering and glass infiltration is disclosed. The method first uses Al2O3 powder to join alumina ceramics to obtain an "alumina / porous Al2O3 / alumina" joint; then, glass solder is used to infiltrate and fill the "alumina / porous Al2O3 / alumina" joint to obtain an "alumina / Al2O3 + microcrystalline glass / alumina" joint, thereby achieving a dense connection of alumina ceramics.

[0007] The particle size of the Al2O3 powder is 20-100 nm.

[0008] The composition of the glass solder, calculated by weight percentage, is as follows: Al2O3: 15-25%, RE2O3: 50-60%, B2O3: 1-5%, SiO2: 15%-25%, ZrO2: 1-5%, TiO2: 1-5%; wherein RE2O3 is one or more of La2O3, Y2O3, Dy2O3 and Ho2O3.

[0009] The method specifically includes the following steps:

[0010] (1) Material preparation: After grinding and polishing the surface of the alumina ceramic to be welded, ultrasonic cleaning is performed for 5-20 minutes with acetone as the medium, and then it is dried for later use.

[0011] (2) Glass solder preparation: Weigh each oxide raw material according to the above composition of glass solder, mix them evenly, and then prepare glass solder powder by melt-water quenching method;

[0012] (3) First step of connection: Al2O3 powder is mixed with anhydrous ethanol to prepare slurry I. Slurry I is uniformly coated on the surface of the alumina ceramic to be welded, and the two surfaces coated with slurry I are tightly bonded together. After drying, a sandwich assembly structure of "alumina ceramic / Al2O3 powder / alumina ceramic" is constructed. The sandwich assembly structure is placed in a muffle furnace with an air atmosphere and rapidly heated to the welding temperature, and held at that temperature for a sufficient time. After the holding time is completed, it is cooled to room temperature with the furnace to obtain an "alumina / porous Al2O3 / alumina" joint. No pressure is used during the connection process.

[0013] (4) Second step of penetration: The glass solder powder prepared in step (2) is mixed with anhydrous ethanol to form slurry II. Slurry II is uniformly coated on the joint surface connected in step (3). After drying, it is placed in a muffle furnace in an air atmosphere and rapidly heated to the penetration temperature. The temperature is kept for a sufficient time to ensure that the glass solder completely penetrates and fills the weld. After the temperature is kept, it is cooled to room temperature at a uniform speed to obtain the "alumina / Al2O3+microcrystalline glass / alumina" joint.

[0014] In step (1) above, the grinding and polishing process is as follows: grinding is carried out in sequence with 400#, 800# and 1200# sandpaper, and then polishing is carried out in sequence with diamond polishing paste with particle sizes of 2.5μm, 1.5μm and 0.5μm.

[0015] In step (2) above, the process of preparing glass solder powder by melt-water quenching is as follows: the weighed oxide raw material powder is placed in a polytetrafluoroethylene ball mill jar, and ball milling is performed using alcohol as the ball milling medium and ZrO2 as the grinding ball. The ball milling speed is 400-500 rpm, and the ball milling time is 2-5 h. After ball milling, the powder is dried, and the dried material is poured into a platinum crucible and placed in a muffle furnace with an air atmosphere and heated to 1500-1600℃. After holding at this temperature for 1-3 h, the resulting glass melt is poured into deionized water to obtain glass fragments. The glass fragments are placed in an agate ball mill jar and ball milled using agate as the grinding ball. The ball milling speed is 400-500 rpm, and the ball milling time is 2-5 h. After ball milling, the powder is dried and passed through a 200-mesh sieve to obtain the glass solder powder for later use.

[0016] In step (3) above, when preparing slurry I, the mass of added ethanol accounts for 40%-60% of the total mass of slurry I.

[0017] In step (3) above, after the sandwich assembly structure is placed in the muffle furnace, it is heated to the welding temperature of 1550-1650℃ at a heating rate of 5-10℃ / min, held for 20-30min, and then cooled to room temperature with the furnace for later use.

[0018] In step (4) above, when preparing slurry II, the mass of added ethanol accounts for 40%-60% of the total mass of slurry II.

[0019] In step (4) above, after the joint coated with slurry II is dried, it is placed in a muffle furnace and heated to a penetration temperature of 1450-1500℃ at a heating rate of 5-10℃ / min, and held for 60-120min. During the cooling process, the cooling rate is 2-10℃ / min.

[0020] The design mechanism and beneficial effects of this invention are as follows:

[0021] 1. The method of this invention first uses the sintering principle to connect alumina ceramics with alumina powder. Then, utilizing the principle of liquid glass penetrating into the intergranular space of dense ceramics, glass solder is used to penetrate and fill the alumina / porous Al2O3 / alumina joint to eliminate weld defects, reduce thermal expansion differences, and improve the high-temperature resistance and thermal shock resistance of the joint, ultimately obtaining a joint with high strength.

[0022] 2. The glass solder used in this invention has excellent intergranular penetration ability, which can not only fill the through holes in the Al2O3 weld layer, but also fill closed pore defects. Ultimately, a dense, defect-free alumina / alumina joint can be obtained.

[0023] 3. This invention can ultimately obtain welds with an Al2O3 content higher than 50%, significantly reducing the difference in thermal expansion coefficients between the weld and the base material. The final difference between the thermal expansion coefficient of the weld and the ceramic base material is no more than 2%. After 100 cycles of thermal shock from room temperature to 1000℃, the joint strength did not decrease significantly.

[0024] 4. This invention can produce a weld seam composed of Al2O3 and a crystalline phase, significantly improving the high-temperature resistance of the joint. The bending strength of the joint at 1000℃ can reach more than 90% of that of the alumina base material. Attached Figure Description

[0025] Figure 1 This is a schematic diagram of a two-step welding process.

[0026] Figure 2 This is a microstructure photograph of the alumina ceramic joint obtained in Example 1.

[0027] Figure 3 The image shows the microstructure of the alumina ceramic joint obtained in Comparative Example 1. Detailed Implementation

[0028] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.

[0029] Example 1

[0030] This embodiment describes a two-step method for joining alumina ceramics based on alumina powder solder sintering and glass infiltration principles. The welding process is as follows: Figure 1 As shown, the specific steps include:

[0031] (1) Material preparation: The surface of the alumina ceramic to be welded was polished with 400#, 800# and 1200# sandpaper in sequence, and then polished with diamond polishing paste with particle sizes of 2.5μm, 1.5μm and 0.5μm in sequence. The polished alumina ceramic was ultrasonically cleaned with acetone for 20 minutes and then dried for later use.

[0032] (2) Preparation of glass solder: The composition of the glass solder used is (wt.%): Al2O3: 15%, Dy2O3: 55%, B2O3: 2%, SiO2: 22%, ZrO2: 3%, TiO2: 3%. The raw materials of each oxide powder were weighed according to the above proportions and placed in a polytetrafluoroethylene ball mill jar. Alcohol was used as the milling medium, and ZrO2 was used as the milling balls. The milling speed was 450 rpm, and the milling time was 4 h. After milling, the raw materials were dried in a vacuum drying oven at 70℃ for 2 h. The dried raw materials were poured into a platinum crucible and heated to 1550℃ in a muffle furnace. After holding at this temperature for 2 h, the glass melt was poured into deionized water to obtain glass fragments. The glass fragments were placed in an agate ball mill jar and milled at 500 rpm for 4 h. After milling, the fragments were dried and passed through a 200-mesh sieve to obtain the glass solder powder, which was then set aside.

[0033] (3) First step of connection: Prepare slurry I by mixing Al2O3 powder and anhydrous ethanol in a 1:1 mass ratio. Coat slurry I evenly onto the surface of the alumina ceramic to be welded, and tightly adhere the two surfaces together. After drying, construct a "alumina ceramic / Al2O3 powder / alumina ceramic" sandwich assembly structure. Place this sandwich assembly structure in an air-atmosphere muffle furnace and heat it to 1550℃ at a heating rate of 8℃ / min, holding it at that temperature for 30 min. After the holding period, allow the joint to cool to room temperature with the furnace. No pressure is used during the connection process;

[0034] (4) Second step of penetration: The glass welding powder prepared in step (2) is mixed with anhydrous ethanol at a mass ratio of 1:1 to form slurry II. Slurry II is uniformly coated on the joint surface connected in step (2). After drying, it is placed in a muffle furnace in an air atmosphere and rapidly heated to 1450°C at a heating rate of 8°C / min, and held at that temperature for 120min to ensure that the glass solder completely penetrates and fills the joint weld. After the holding time is completed, the joint is cooled to room temperature at a rate of 5°C / min.

[0035] Figure 2 This is a microstructure photograph of the alumina ceramic joint obtained in Example 1. By using glass solder for infiltration and filling, the entire weld became complete and defect-free. Simultaneously, due to the slow cooling rate, the glass phase in the weld was able to fully crystallize. Overall, the distribution of each phase in the weld was relatively uniform. Using image analysis software, it was confirmed that in this example, Al2O3, the crystalline phase Dy2Si2O7, and the residual glass phase accounted for approximately 52.7%, 47.2%, and 0.1% of the total mass of the composite weld, respectively. Calculations using the mixing principle showed that the coefficient of thermal expansion of the weld in this example was 7.89 × 10⁻⁶. -6The difference in strength from the base material is only 2% at / ℃. The "alumina / Al2O3 + microcrystalline glass / alumina" joint prepared in Example 1 achieves a room temperature flexural strength of 322 MPa, which is essentially the same as that of general commercial alumina ceramics. Its flexural strength at 1000℃ reaches 145 MPa, exceeding 90% of that of the alumina base material under the same conditions. After 100 cycles of thermal shock at room temperature and 1000℃, the joint still retains a strength of 320 MPa, comparable to its room temperature strength.

[0036] Example 2

[0037] The difference from Example 1 is that the heating time in step (3) is changed to 25 minutes, while the other steps are the same as in Example 1. The joint obtained in this example has a room temperature bending strength of 308 MPa. The bending strength at 1000℃ is 135 MPa. After 100 cycles of thermal shock at room temperature and 1000℃, the joint strength did not decrease significantly.

[0038] Example 3

[0039] The difference from Example 1 is that the connection temperature in step (3) is changed to 1600℃, while the other steps are the same as in Example 1. The joint obtained in this example has a room temperature bending strength of 315MPa. The bending strength at 1000℃ is 138MPa. After 100 cycles of thermal shock at room temperature and 1000℃, the joint strength did not decrease significantly.

[0040] Example 4

[0041] The difference from Example 1 is that the heating time in step (4) is changed to 60 min, while the other steps are the same as in Example 1. The joint obtained in this example has a room temperature bending strength of 318 MPa. The bending strength at 1000℃ is 140 MPa. After 100 cycles of thermal shock at room temperature and 1000℃, the joint strength did not decrease significantly.

[0042] Example 5

[0043] The difference from Example 1 is that the penetration temperature in step (4) is changed to 1500℃, while the other steps are the same as in Example 1. The joint obtained in this example has a room temperature bending strength of 311MPa. The bending strength at 1000℃ is 141MPa. After 100 cycles of thermal shock at room temperature and 1000℃, the joint strength did not decrease significantly.

[0044] Example 6

[0045] The difference from Example 1 is that in step (2), Dy2O3 in the glass solder composition is replaced with an equal mass of La2O3, while the other steps are the same as in Example 1. The precipitated crystals in the joint weld obtained in this example are mainly La2Si2O7. The bending strength of the joint at room temperature is 303 MPa. The bending strength at 1000℃ is 133 MPa. After 100 cycles of thermal shock at room temperature and 1000℃, the joint strength did not decrease significantly.

[0046] Example 7

[0047] The difference from Example 1 is that in step (2), Dy2O3 in the glass solder composition is replaced with an equal mass of Y2O3, while the other steps are the same as in Example 1. The precipitated crystals in the joint weld obtained in this example are mainly Y2Si2O7. The joint's room temperature bending strength is 315 MPa. The bending strength at 1000℃ is 134 MPa. After 100 cycles of thermal shock at room temperature and 1000℃, the joint strength did not decrease significantly.

[0048] Comparative Example 1

[0049] This comparative example uses a 1:1 weight ratio of Al2O3 and glass solder to bond alumina ceramics. Step (1) material preparation and step (2) glass solder preparation are the same as in Example 1.

[0050] Step (3) Joint connection: Equal weights of Al2O3 powder and glass solder powder are mixed to obtain a mixed solder; then the mixed solder is mixed with anhydrous ethanol at a mass ratio of 1:1 to prepare a slurry. The slurry is uniformly coated on the surface of the alumina ceramic to be welded, and after drying, a "sandwich" assembly structure is constructed. The assembled joint is placed in a muffle furnace with an air atmosphere and rapidly heated to 1550℃, and held at that temperature for 120 minutes. After the holding period, the joint is cooled to room temperature with the furnace.

[0051] No pressure is used during the connection process;

[0052] Figure 3 This is a microstructure photograph of the alumina joint obtained in Comparative Example 1. Due to the introduction of high-melting-point Al2O3 powder reducing the wettability of the mixed solder on the alumina ceramic surface, the joint obtained using the Al2O3 / glass mixed solder exhibits numerous porosity defects.

[0053] Comparative Example 2

[0054] The difference from Example 1 is that the cooling rate in step (4) is changed to 50℃ / min, while the other steps are the same as in Example 1. The joint obtained in this example has a room temperature bending strength of 312MPa. However, due to the use of a faster cooling rate, the glass phase content in the weld is higher, and the bending strength at 1000℃ is only 32MPa.

[0055] The mechanical property data of the joints obtained in Examples 1-7 and Comparative Examples 1-2 are shown in Table 1. As can be seen from the table, Examples 1-7 all achieved excellent room temperature strength, high temperature strength, and strength after thermal shock cycling. Comparative Example 1 had the lowest room temperature strength due to the failure to form an effective connection. Comparative Example 2 had lower high temperature strength due to the higher glass phase content in the weld.

[0056] Table 1. Joint bending strength data of the embodiments and comparative examples.

[0057]

Claims

1. A two-step method for joining alumina ceramics based on the principles of alumina powder solder sintering and glass infiltration, characterized in that: This method first uses Al2O3 powder to pre-bond alumina ceramics to obtain an "alumina / porous Al2O3 / alumina" joint; then, glass solder is used to penetrate and fill the "alumina / porous Al2O3 / alumina" joint. After penetration and filling, the joint is cooled to room temperature at a uniform rate of 2-10℃ / min. After cooling, a dense connection of the alumina ceramics is achieved. The process of pre-bonding the alumina ceramics is as follows: Al2O3 powder is mixed with anhydrous ethanol to prepare slurry I. Slurry I is uniformly coated on the alumina ceramic surface to be welded, and the two surfaces to be welded are tightly bonded together. After welding, an "alumina / porous Al2O3 / alumina" joint is obtained. The composition of the glass solder, calculated by weight percentage, is as follows: Al2O3: 15-25%, RE2O3: 50-60%, B2O3: 1-5%, SiO2: 15%-25%, ZrO2: 1-5%, TiO2: 1-5%.

2. The two-step bonding method for alumina ceramics based on alumina powder solder sintering and glass infiltration principle according to claim 1, characterized in that: The particle size of the Al2O3 powder is 20-100 nm.

3. The two-step bonding method for alumina ceramics based on alumina powder solder sintering and glass infiltration principle according to claim 2, characterized in that: In the glass solder composition, RE2O3 is one or more of La2O3, Y2O3, Dy2O3 and Ho2O3.

4. The two-step bonding method for alumina ceramics based on alumina powder solder sintering and glass infiltration principle according to claim 2, characterized in that: The method specifically includes the following steps: (1) Material preparation: After grinding and polishing the surface of the alumina ceramic to be welded, ultrasonic cleaning is performed with acetone as the medium for 5-20 minutes, and then it is dried for later use. (2) Glass solder preparation: Weigh each oxide raw material according to the composition of the glass solder, mix them evenly, and then prepare glass solder powder by melt-water quenching method; (3) First step of connection: Al2O3 powder is mixed with anhydrous ethanol to prepare slurry I. Slurry I is uniformly coated on the alumina ceramic surface to be welded, and the two surfaces to be welded are tightly attached. After drying, a sandwich assembly structure of "alumina ceramic / Al2O3 powder / alumina ceramic" is constructed. The sandwich assembly structure is placed in a muffle furnace and rapidly heated to the welding temperature in an air atmosphere, and held for 20-30 minutes. After the holding time is completed, it is cooled to room temperature with the furnace to obtain the "alumina / porous Al2O3 / alumina" joint. No pressure is used during the connection process. (4) Second step of penetration: Mix the glass solder powder prepared in step (2) with anhydrous ethanol to form slurry II. Apply slurry II evenly to the joint surface connected in step (3). After drying, place it in a muffle furnace and heat it to the penetration temperature in an air atmosphere. Keep it at the temperature for 60-120 minutes to ensure that the glass solder completely penetrates and fills the weld. After the heat preservation is completed, the joint is cooled to room temperature at a uniform speed.

5. The two-step bonding method for alumina ceramics based on the principles of alumina powder solder sintering and glass infiltration according to claim 4, characterized in that: In step (1), the grinding and polishing process is as follows: grinding is carried out with 400#, 800# and 1200# sandpaper in sequence, and then polishing is carried out with diamond polishing paste with particle sizes of 2.5μm, 1.5μm and 0.5μm in sequence.

6. The two-step bonding method for alumina ceramics based on the principles of alumina powder solder sintering and glass infiltration according to claim 4, characterized in that: In step (2), the process of preparing glass solder powder by the melt-water quenching method is as follows: the weighed oxide raw material powder is placed in a polytetrafluoroethylene ball mill jar, and ball milling is performed using alcohol as the ball milling medium and ZrO2 as the grinding ball. The ball milling speed is 400-500 rpm, and the ball milling time is 2-5 h. After ball milling, the powder is dried, and the dried material is poured into a platinum crucible and placed in a muffle furnace with an air atmosphere and heated to 1500-1600℃. After holding at this temperature for 1-3 h, the resulting glass melt is poured into deionized water to obtain glass fragments. The glass fragments are placed in an agate ball mill jar and ball milled using agate as the grinding ball. The ball milling speed is 400-500 rpm, and the ball milling time is 2-5 h. After ball milling, the powder is dried and passed through a 200-mesh sieve to obtain the glass solder powder for later use.

7. The two-step bonding method for alumina ceramics based on alumina powder solder sintering and glass infiltration principle according to claim 4, characterized in that: In step (3), when preparing slurry I, the mass of added ethanol accounts for 40%-60% of the total mass of slurry I.

8. The two-step bonding method for alumina ceramics based on alumina powder solder sintering and glass infiltration principle according to claim 4, characterized in that: In step (3), after the sandwich assembly structure is placed in the muffle furnace, it is heated to the welding temperature of 1550-1650℃ at a heating rate of 5-10℃ / min, and then cooled to room temperature with the furnace after the heat preservation is completed.

9. The two-step bonding method for alumina ceramics based on the principles of alumina powder solder sintering and glass infiltration according to claim 4, characterized in that: In step (4), when preparing slurry II, the mass of added ethanol accounts for 40%-60% of the total mass of slurry II.

10. The two-step bonding method for alumina ceramics based on alumina powder solder sintering and glass infiltration principle according to claim 4, characterized in that: In step (4), after the joint coated with slurry II is dried, it is placed in a muffle furnace and heated to a penetration temperature of 1450-1500℃ at a heating rate of 5-10℃ / min.

Citation Information

Patent Citations

  • Al2O3-Dy2O3-SiO2 ternary system rare-earth sealing material and preparation method of glass sealing ring thereof

    CN101759367A

  • Two-step aluminum oxide ceramic connecting method based on aluminum oxide powder solder sintering and glass permeation principle

    CN118754698A